Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Lin, Shihui; Gao, Xiaolong; Zhang, Mo; Lyu, Mingxin; Ke, Caihuan (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, Pacific abalone (Haliotis discus hannai) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or improve food availability, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help understand these rhythmic behaviors. In this study, quantification of behavioral data for abalone and its predator Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggested that the distance of moving, duration of moving, percentage of feeding individuals, and cumulative duration of feeding by abalones were significantly lower under short-term predation risk than long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK), and expression levels of 5-HT1A receptor and 5-HT2 receptor were significantly higher under long-term predation risk than short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen contents of abalones were significantly higher under short-term predation risk than long-term predation risk, thereby implying roles for anaerobic metabolism and aerobic metabolism as primary energy sources under short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under short-term predation risk, but changes in the movement and feeding behaviors of abalones still only occurred at night. Correlation analysis showed that the expression levels of Bmal1 and Clock had significant positive correlations with the circadian changes in the movement parameters of abalones, thereby suggesting a dominant role for the rhythmic expression of endogenous circadian clock genes in regulating the rhythmic behavior of abalones. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals, as well as providing a reference for developing rational enhancement and release plans, and improving the level of protection for marine benthic biodiversity.